Children’s Hope Symbolized by Jack Frost’s Motivation to be A True Guardian in Peter Ramsey’s Film “Rise of The Guardians” - Guruh Praja Wijayanto; Haryati Sulistyorini (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2020)
Abstract: This thesis entitled Children’s Hope Symbolized by Jack Frost’s Motivation to be A True Guardian in Peter Ramsey’s Film “Rise of The Guardians” has set a goal at finding semiotic elements of sign of motivation to become the true guardian experienced by Jack Frost as the main character described in film. In conducting the research, descriptive qualitative used to find semiotic aspect to find semiotic aspect of Children Hope’s Symbolized by Jack Frost Motivation to be A True Guardian. The approaches that are used by the researcher are divided into two to analyze the data. They are structural approach and semiotic approach. The researcher used a structural approach to analyze structural elements such as plot, main character traits of the main character, conflict experienced by the main character, and setting described in this story. Semiotic approach used to describe signs that consist of icon, index, symbol to analyze appearance of signs that reflect main character motivation to become a true guardian. This research shows the plot of Peter Ramsey’s film Rise of the Guardians consist of exposition, rising actions, climax, falling action, and resolution. The main character of Peter Ramsey’s film Rise of the Guardians is Jack Frost. Jack described has 6 traits such as Self-Doubt, Mischievous, Hesitant, Caring, Persistent, Generous. In this film, the main character Jack Frost has experienced internal and external conflict. The setting in film is divided into setting of place and setting of time. The Setting of the place is Frozen Pond Town. North Pole, Jamie’s House. Tooth Palace, Warren, Pitch Lair. The setting of times is 300 years after Jack’s revival, Snow day, Day/Noon, Evening, Night. Last is about signs that appear at Peter Ramsey’s film Rise of the Guardians classified into Icon, index, symbol. The icons that show in the film are Jack’s staff, The Globe of Belief, Jack’s Gold Box, Nesting Doll, Oath Book/Guardians oath, Sandy’s sand and Pitch sand. The Index shows in film are Jack's first thing to remember after revival, freezing something, Good dream becoming Bad dream (Nightmare), North advice, Jack’s sister voice, fixing staff, Denying and Accepting oath. The symbol shows in film are Frozen Pond, G shaped Jack’s staff, Recall memory, Man in the moonlight. Symbol Recall memory becomes the result of Jack being motivated to become a true Guardian that has correlation with analysis, structural aspects, and other semiotics aspects.